1999
DOI: 10.1037/0022-006x.67.2.243
|View full text |Cite
|
Sign up to set email alerts
|

A test of behavioral family therapy to augment exposure for combat-related posttraumatic stress disorder.

Abstract: This study tested a family-based skills-building intervention in veterans with chronic combat-related posttraumatic stress disorder (PTSD). Veterans and a family member were randomly assigned to 1 of 3 conditions: (a) waiting list, (b) 18 sessions of twice-weekly exposure therapy, or (c) 18 sessions of twice-weekly exposure therapy followed by 16 sessions of behavioral family therapy (BFT). Participation in exposure therapy reduced PTSD positive symptoms (e.g., reexperiencing and hyperarousal) but not PTSD neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
127
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 182 publications
(132 citation statements)
references
References 66 publications
3
127
1
1
Order By: Relevance
“…Both were conducted with samples of male combat Veterans and their family members. As previously reviewed, in another published RCT including BFT after DTE, Glynn and colleagues found that those receiving DTEBFT had significantly more improvements in interpersonal problem-solving than those who did not receive BFT [4].…”
Section: Sautter Et Al 2009 [30]mentioning
confidence: 87%
See 3 more Smart Citations
“…Both were conducted with samples of male combat Veterans and their family members. As previously reviewed, in another published RCT including BFT after DTE, Glynn and colleagues found that those receiving DTEBFT had significantly more improvements in interpersonal problem-solving than those who did not receive BFT [4].…”
Section: Sautter Et Al 2009 [30]mentioning
confidence: 87%
“…Evidence that the intervention is effective is lacking or poor quality, or conflicting, and the balance of benefits to harms cannot be determined" [8, p. 202]. The supporting evidence offered for this conclusion includes three studies: Devilly [9], Glynn et al [4], and Monson et al [10]. Upon review of these studies, the CPG summarizes that "BFT [behavioral family therapy] did not significantly improve the PTSD symptoms and was inferior to other psychotherapies" [8, p. 144].…”
Section: Va/dod Clinical Practice Guideline Regarding Couple/family mentioning
confidence: 99%
See 2 more Smart Citations
“…In recognition of this fact, family concepts and therapy have appeared in the clinical traumatic stress literature. However, in the only controlled study of its kind, behavioral family therapy did not improve outcomes of an exposure-based treatment of combat-related PTSD without SUD (Glynn et al, 1999).…”
Section: Introductionmentioning
confidence: 84%